White Wine—Induced Endothelium-Dependent Vasorelaxation in Sprague-Dawley Rats - Zrinka Mihaljević; Toni Kujundžić; Vladimir Jukić; Ana Stupin; Mato Drenjančević; Ines Drenjančević (Antioxidants, 2022)
The vasodilatory activity and polyphenolic content of commercially available white wine is low compared to red wines. This study assessed the vasodilator potential of white wines produced by four different fermentation processes: (1) white wine produced by the standard procedure; (2) grapes left to macerate completely for 30 days; (3) grapes left to macerate up to half of unfermented sugar; and (4) wine produced by cooling the must. All tested wine samples were analyzed for their phenolic content, antioxidant capacity, and ethanol content. Vasodilation was examined in the norepinephrine pre-contracted isolated rat aortas of male Sprague-Dawley rats randomly exposed to cumulative concentrations (0.1‰ to 8‰ final dilutions in organ baths) of each of the tested wine samples with or without quercetin and/or gallic acid supplementation, in the absence/presence of NOS inhibitor L-NAME. Standard procedure and the procedure involving must cooling gives wine with lower phenolic content, antioxidant capacity, and lower vasodilator potential, respectively. L-NAME inhibited vasodilation to all wine samples. Quercetin with or without gallic acid supplementation restored vasodilation. Results show that vasodilation to white wine is NO-dependent and suggest the possibility of increasing the antioxidant capacity and vasodilatory potential of white wine using different production procedures, depending on quercetin content.